Joint Research on Clock Synchronization and Localization in Wireless Sensor Network with Stochastic Exponentially Distributed Noise - Xiang Zhao; Jiming Lin (Dianxin kexue)
Joint clock synchronization and localization based on the time of arrival（TOA）measurements is a very important research topic for many wireless sensor network applications. The exponentially distributed link delay is usually used to describe the practical network link condition. The joint maximum likelihood estimation（JMLE）on clock synchronization and localization problem was first proposed based on the TOA measurements. JMLE was optimal only for Gaussian delay, as for the exponentially distributed delay, the joint best linear unbiased estimation （JBLUE）was then proposed. The result is derived via simulation: JMLE and JBLUE are always superior to the latest joint algorithm, with the highest estimation accuracy.